MEDIA PEMBELAJARAN INTERAKTIF SENI BUDAYA PADA SMK DB 4 KOTA JAMBI: Learning Media, Cultural Arts, Adobe Flash CS6 - Wati, Nila; Riswan, Riswan; yanti, Yuli (JURNAL AKADEMIKA, 2025)
Schools are institutions for teaching students under the supervision of teachers. In formal education schools that are generally compulsory, in this system students go through a series of teaching and learning activities in schools. In a school there are courses in Art and Culture. To assist students in improving the understanding of the material conveyed by the teacher, by using interactive learning media that are currently highly developed in the world of education. That way researchers are interested in making Interactive Arts and Culture Learning Media at SMK 4 Jambi City. By using the Adobe Flash Professional CS6 application, Adobe After Effect.This application displays features of images, text, sound, animation, audio and is equipped with evaluation. This learning media application can help students in the learning process.